Associations between the Application of Signature Character Strengths, Health and Well-being of Health Professionals - Hausler, Melanie; Strecker, Cornelia; Huber, Alexandra; Brenner, Mirjam; Höge, Thomas; Höfer, Stefan (Frontiers in Psychology, 2017)
Previous research has shown a positive relation between character strengths, well-being and health. The aim of this analysis was to identify relations between the application of signature character strengths (ASCS) at work, and well-being and health, among medical students (study 1) and resident physicians (study 2). We expected positive direct links between the constructs and indirect effects through emotional exhaustion. To test these hypotheses, 387 medical students in their first year and 136 resident physicians completed five scales measuring well-being, mental/ physical health, character strengths, the application of their five individual signature strengths, and emotional exhaustion as an indicator of burnout. Partial correlations were examined, and mediation analyses performed. ASCS at work was positively linked with well-being and mental health but not with physical health. All links were mediated by emotional exhaustion in study 1 and (except for mental health) also in study 2. Future studies would therefore do well to investigate the promotion of ASCS at work of people operating in medical education and its potential in fostering well-being and preventing burnout from the outset.